2014
DOI: 10.1053/j.ajkd.2013.10.061
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Albumin Excretion Rate Versus Urine Albumin-Creatinine Ratio for the Assessment of Albuminuria: A Diagnostic Test Study From the Prevention of Renal and Vascular Endstage Disease (PREVEND) Study

Abstract: Background The albumin-creatinine ratio (ACR) in spot urine samples is recommended for albuminuria screening instead of measured albumin excretion rate (mAER) in 24-hour urine collections. In those with extremes of muscle mass, differences in spot urine creatinine may lead to under- or over-estimation of mAER by ACR. We hypothesized that calculating estimated AER (eAER) using spot ACR and estimated creatinine excretion rate (eCER) may improve albuminuria assessment. Study Design Diagnostic test study. Sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 19 publications
(21 reference statements)
1
32
0
Order By: Relevance
“…This could have led to misclassification. The PREVEND study reported that ACR was less accurate and more biased than eAER, 24 because urinary creatinine is influenced by muscle mass, introducing confounding based on non-albuminuric covariates. 25 However, in a sensitivity analysis our results were consistent when utilizing eAER as a predictor.…”
Section: Discussionmentioning
confidence: 99%
“…This could have led to misclassification. The PREVEND study reported that ACR was less accurate and more biased than eAER, 24 because urinary creatinine is influenced by muscle mass, introducing confounding based on non-albuminuric covariates. 25 However, in a sensitivity analysis our results were consistent when utilizing eAER as a predictor.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, the bias of the eAER calculated by eCER using CKD-EPI formula[13] was higher at 3.8 mg/24 h. This study did not assess any other formulae. Abdelmalek et al[21] also showed improved bias of CKD-EPI (median bias -1.0 mg/g), Fotheringham (-0.9 mg/g) and Walser (-0.8 mg/g) as compared to ACR (-2.3 mg/g). This study also revealed improved accuracy of the above three formulae as compared to ACR.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, the accuracy of ACR and PCR improved after adjusting for muscle mass using eCER. Previous studies have focused on the superiority of eAER over ACR in the accuracy of albuminuria assessment [15,21]. Automated eAER reporting should be applied to expand the use of eAER in clinical practice [10].…”
Section: Discussionmentioning
confidence: 99%
“…Daily albuminuria and proteinuria were measured from 24-h urine collection, and estimated albumin excretion rate (eAER) and estimated protein excretion rate (ePER) were calculated from ACR and PCR, respectively, by multiplying estimated creatinine excretion rate (eCER) [10,15]. eCER MDRD and eCER CKD-EPI were derived from MDRD and CKD-EPI equation, and eAER MDRD , eAER CKD-EPI , ePER MDRD , and ePER CKD-EPI were calculated to estimate daily proteinuria and albuminuria [12].…”
Section: Measurementsmentioning
confidence: 99%